(untitled) (EDUCATION IN THE 21ST CENTURY, 2024)
The aim of our research is to study and present the peculiarities of teaching the subject "History of the Armenian Press of Constantinople", the problems fixed within the subject. In this regard, we consider necessary theoretical, practical and methodological innovative approaches in this direction. Approaches to teaching the subject in curricula are different։ we have considered those features, manifestations, main approaches, justifying the approach that we practically apply in teaching the subject. As a result of the lack of an interdisciplinary approach to the subject, the understanding of the applied area of the subject is impaired in both professionals and students. The subject is specific, which implies a flexible approach, as a result of which the purpose of teaching the subject, problems, efficiency, and learning outcomes will not be affected. Our study was based on the collection of statistical data, their generalization, classroom tests that we observed and recorded during the years of teaching the subject. The problems presented in the article are our long-term observations. One of the most important problems of the subject is not to present the scope of the course, since, as we have already mentioned, the approach to considering the subject from interdisciplinary aspects is violated. Having set a number of challenges for the experts and students, we give our final conclusions, one of which is that the subject needs to be rethought and considered from new perspectives. In this context, we also considered the issue that knowledge of Western Armenian would be a desirable prerequisite for learning. Taking into account the problems and characteristics of the subject, we present our methodological approaches and observations that we use in the teaching process. Since the approaches to teaching the subject are different, and there are also different ideas associated with the field of application, the subject acquires special importance, interdisciplinary significance. As a result of a comprehensive consideration of the subject, vague ideas about the scope of the subject and its effectiveness will also be resolved. This will also address the need to maintain the influence of the subject among students.